The Synergistic Effects of Polysaccharides and Ginsenosides From American Ginseng (Panax quinquefolius L.) Ameliorating Cyclophosphamide-Induced Intestinal Immune Disorders and Gut Barrier Dysfunctions Based on Microbiome-Metabolomics Analysis - Zhou, Rongrong; He, Dan; Xie, Jing; Zhou, Qingyijun; Zeng, Hongliang; Li, Hongmei; Huang, Luqi (Frontiers in Immunology, 2021)
Cyclophosphamide (CTX), used in cancer chemotherapy, a high dose of which would cause immunosuppressive effect and intestinal mucosa damage. American ginseng (Panax quinquefolius L.) has long history of functional food use for immunological disorder, colitis, cancer and so on. This study aimed to illustrate the underlying mechanism of American ginseng’s immunomodulatory effect in CTX-induced mice. In this study, all groups of American ginseng (American ginseng polysaccharide, AGP; American ginseng ginsenoside, AGG; co-treated with American ginseng polysaccharide and ginsenoside, AGP_AGG) have relieve the immune disorder by reversing the lymphocyte subsets ratio in spleen and peripheral blood, as well as stimulating CD4+T cells and IgA-secreting cells in small intestine. These three treatment groups, especially AGP_AGG co-treated group recovered the intestine morphology that up-regulated villus height (VH) /crypt depth (CD) ratio, areas of mucins expression, quantity of goblet cells, and expression of tight junction proteins (ZO-1, occludin). Importantly, the microbiome-metabolomics analysis was applied in this study to illustrate the possible immuno-modulating mechanism. The synergistic effect of polysaccharides and ginsenosides (AGP_AGG group) restored the gut microbiota composition and increased various beneficial mucosa-associated bacterial taxa Clostridiales, Bifidobacterium, and Lachnospiraceae, while decreased harmful bacteria Escherichia−Shigella and Peptococcaceae. Also, AGP_AGG group altered various fecal metabolites such as uric acid, xanthurenic acid, acylcarnitine, 9,10-DHOME, 13-HDoHE, LysoPE15:0, LysoPC 16:0, LysoPI 18:0 et al that associated with immunometabolism or protective effect of gut barrier. These results suggest AG, particularly co-treated of polysaccharide and ginsenoside, may be used as immunostimulants targeting microbiome-metabolomics axis to prevent CTX-induced side effects in cancer patients.